Students’ Perception Toward the Use of Educandy in Learning English Vocabulary at SMPN 1 Maiwa - Widia lestari; Ibrahim Manda; Nurul Faradillah; Sitti Aisa; hermansyah, sam (Edumaspul: Jurnal Pendidikan, 2026)
This study investigated students’ perceptions toward the use of Educandy in learning English vocabulary at SMPN 1 Maiwa. The research aimed to explore how students perceived the implementation of Educandy as a game-based learning platform and to identify the internal and external factors influencing their perceptions. A qualitative descriptive design was employed in this study. The participants consisted of 20 eighth-grade students, while five students were purposively selected for in-depth interviews. Data were collected through semi-structured interviews, questionnaires, classroom observation, and documentation. The data were analyzed using Miles, Huberman, and Saldaña’s interactive model, including data reduction, data display, and conclusion drawing. The findings revealed that students had positive perceptions toward the use of Educandy in vocabulary learning. Students reported that Educandy made learning more enjoyable, interactive, motivating, and easier to understand compared to traditional vocabulary learning methods. The platform also increased students’ engagement, participation, and confidence during classroom activities. In addition, interactive features such as matching games, quizzes, and word puzzles supported vocabulary retention through repetition and active learning. The study further found that students’ perceptions were influenced by internal factors, including motivation, interest, confidence, and learning preferences, as well as external factors such as teacher support, instructional strategies, classroom environment, and the characteristics of the learning media. Among these factors, external factors showed a slightly stronger influence on students’ positive perceptions. In conclusion, Educandy can be considered an effective game-based learning medium that supports vocabulary learning and enhances students’ learning experiences in English classes.